2022
DOI: 10.3390/ijerph192214632
|View full text |Cite
|
Sign up to set email alerts
|

Do Young People Perceive E-Cigarettes and Heated Tobacco as Less Harmful Than Traditional Cigarettes? A Survey from Poland

Abstract: New tobacco and nicotine-containing products are gaining more popularity among young people. The aim of this study is to assess the prevalence in the perception of e-cigarettes and heated tobacco among young people in Poland and to assess the factors that are positively correlated with this perception. A cross-sectional study covering almost 12,000 adolescents aged 13–18 was carried out in January and February 2020. Data were collected through a detailed questionnaire recommended for monitoring tobacco use by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Heated tobacco products, which used closed heating instead of combustion to distill and release tobacco components, became an important new type of tobacco product due to their significantly reduced harmful substances and lack of smoldering ( Enomoto et al, 2022 ; Watts et al, 2022 ; Wezyk-Caba et al, 2022 ; Yamamoto et al, 2022 ; Yuki et al, 2022 ; Kusonic et al, 2023 ; Vukas et al, 2023 ; Zhao et al, 2023 ). The heating temperature was generally around 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Heated tobacco products, which used closed heating instead of combustion to distill and release tobacco components, became an important new type of tobacco product due to their significantly reduced harmful substances and lack of smoldering ( Enomoto et al, 2022 ; Watts et al, 2022 ; Wezyk-Caba et al, 2022 ; Yamamoto et al, 2022 ; Yuki et al, 2022 ; Kusonic et al, 2023 ; Vukas et al, 2023 ; Zhao et al, 2023 ). The heating temperature was generally around 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Another study in Denmark found that 26.5% of respondents aged 15-17 years had at least tried e-cigs and 1.1% HTPs. Finally, a recent survey from Poland [23] reported that 57.8% of respondents (aged 15-19 years old) have used e-cigs and about 44% HTPs, from which 37.9% and 12.6%, respectively, were never smokers of conventional cigs.…”
Section: Prevalence Of Ever Use Of Novel Tobacco and Nicotine Product...mentioning
confidence: 99%
“…Common reasons to start using e-cigs in all population groups include perceived safety [23,34], novelty and curiosity [12], peer influences, avoidance of smoking regulations [34], and social acceptability [9,35]. However, some generational differences exist.…”
Section: Reasons To Start Using Novel Tobacco and Nicotine Productsmentioning
confidence: 99%
See 2 more Smart Citations